observe-interpret-shape: Evaluation of a model for school development (Pedagogical Horizons, 2020)
The aim of the research project was to evaluate the BIG model (observe - interpret - design) developed on the basis of Bion's learning through experience (Bions 1992) and to demonstrate the possible added value for the professionalization process in the context of practical school studies. At the same time, the motivations of the teachers who had initially decided not to participate in the implementation of the model were asked.
Keywords: school development; professionalization